Danger signals in traumatic hemorrhagic shock and new lines for clinical applications - Dufour-Gaume, Frédérique; Frescaline, Nadira; Cardona, Venetia; Prat, Nicolas J. (Frontiers in Physiology, 2023)
Hemorrhage is the leading cause of death in severe trauma injuries. When organs or tissues are subjected to prolonged hypoxia, danger signals—known as damage-associated molecular patterns (DAMPs)—are released into the intercellular environment. The endothelium is both the target and a major provider of damage-associated molecular patterns, which are directly involved in immuno-inflammatory dysregulation and the associated tissue suffering. Although damage-associated molecular patterns release begins very early after trauma, this release and its consequences continue beyond the initial treatment. Here we review a few examples of damage-associated molecular patterns to illustrate their pathophysiological roles, with emphasis on emerging therapeutic interventions in the context of severe trauma. Therapeutic intervention administered at precise points during damage-associated molecular patterns release may have beneficial effects by calming the inflammatory storm triggered by traumatic hemorrhagic shock.